Lower respiratory rate during sleep in children with Angelman syndrome compared to age-matched controls - Leo Gschwind; Sebastian Camillo Holst; David Nobbs; Florian Lipsmeier; Katalin Buzasi; Ponghatai Boonsimma; Alexander Rotenberg; Vitaliy Kolodyazhniy; Jörg Felix Hipp (Orphanet Journal of Rare Diseases)
Abstract Background Angelman syndrome (AS) is a rare genetic neurodevelopmental disorder caused by the absence of a functional UBE3A gene, leading to developmental, behavioral, and medical challenges. Sleep disturbances, including sleep-disordered breathing, are common in AS. This study, for the first time, investigates nocturnal respiration in individuals with AS and healthy controls at home in a long term setting. Methods A non-invasive ballistocardiography-based (BCG) sleep monitoring device (“sleep mat”) placed under the participants’ mattresses, was used to remotely monitor children with AS aged 1 to 12 years (6.0 ± 3.2 years, n = 40) and age-matched typically developing controls (TDC) (6.2 ± 3.5 years, n = 20) for approximately 12 months. The sleep mat recorded physiological signals during times in bed. We applied fast-Fourier transformation (FFT) to exclude segments without a clear respiratory signal, thereby minimizing the impact of large body movements, wakefulness, or seizure activity. Moreover, polysomnography (PSG) was collected for up to three nights for each participant in their home. Clinical characteristics, genotype, and Bayley Scales of Infant and Toddler Development® (Bayley-III) were also analyzed. Results The average median BCG-derived respiratory rate over the entire study duration was significantly lower in AS compared to TDCs (Cohen’s d = 1.31). PSG-derived respiration data corroborated the lower breathing rate in AS (Cohen’s d = 0.77) and revealed a strong correlation between BCG and PSG derived respiration (r = 0.85) and thus a strong convergent validity of the sleep mat against “gold standard” measures. Next, we defined two groups of AS individuals based on their respiratory rates: a normal respiration group with rates above the minimum in TDC, and a low respiratory rate group with rates below the TDC group’s minimum. A higher prevalence of respiratory abnormalities was observed in deletion carriers (55.2%) versus non-deletion carriers (9.1%). Pulse oximetry data indicated lower oxygen saturation levels in AS individuals (Cohen’s d = 1.60). Moreover, lower Bayley-III scores were observed in the low respiration group, suggesting a link between respiratory dysfunction and neurodevelopmental outcomes in AS. Medication use, particularly antiepileptic drugs, was found to suppress respiratory rates, highlighting the complex interplay between concomitant medication use, genotype, and sleep in AS. Conclusion Our study provides the first long-term observational evidence of a persistent bradypnea-like phenotype in individuals with AS, which may have significant implications for their clinical management. The successful use of the sleep mat device as a non-invasive physiological ambulatory monitoring tool demonstrates its potential as a digital health technology for detecting respiratory abnormalities in pediatric neurodevelopmental disorders. These findings should be further assessed and may have biomarker and clinical utility in AS, particularly in relation to seizure management and cognitive development.